The tadpole of the Narrow-mouthed Frog Microhyla fissipes from Vietnam (Anura: Microhylidae) - Hendrix, Ralf; Gawor, Anna; Vences, Miguel; Ziegler, Thomas (Zootaxa, 2008)
Based on recent mtDNA analyses, Microhyla fissipes Boulenger was removed from the synonymy with M. ornata (Duméril & Bibron) by Matsui et al. (2005),where previously it had been placed by Parker (1934). M. fissipes inhabits southern China (type locality: Taiwan) and large parts of Southeast Asia, including the north-ern Malay Peninsula (Matsui et al. 2005). As a contribution to future comprehensive revisions of larval mor-phology of Microhyla Tschudi, we here provide a detailed description of external morphology of reliably identified tadpoles recently collected from the Truong Son mountain range, central Vietnam.